An ultra-thin double-functional metasurface patch antenna for UHF RFID applications - Koohestani, Mohsen (Sci Rep, 2021)
An ultra-thin double-functional metasurface patch antenna (MPA) was proposed, where it can operate not only in the antenna mode but also can simultaneously act as perfect absorber for normal incident waves, suitable for RFID applications in the 868 MHz band. The MPA structure consists of a typical coaxially-fed patch antenna merged, for the first time, with a metasurface absorber acting as artificial ground. A methodology for the unit-cell design of the metasurface is proposed followed by an equivalent circuit model analysis, which makes it possible to transform a low-loss ([Formula: see text] ) unit-cell with highly-reflective characteristics to a perfect absorber for normal incident waves. It is based on modifying the critical external coupling by properly introducing slits on the unit-cell, allowing to design an ultra-thin ([Formula: see text] at 868 MHz) and a very compact structure in comparison to previously developed designs. For validation purposes, the MPA was fabricated and its performances in both functional modes were characterized numerically and experimentally. It is demonstrated that merging the absorber with the patch not only allows obtaining a well-matched ([Formula: see text]  dB) antenna with an enhanced gain (by 175.6% compared to a typical patch) at the desired frequency but also leads to an overall thickness of only 2.5 mm ([Formula: see text] at 868 MHz). With an absorber size limited to the MPA dimensions, a reasonable 1.3 dB reduction in powers reflected by the MPA was achieved compared to a similar size metallic sheet. Whilst having the lowest profile among the so far reported RFID readers, the proposed MPA can be conveniently fitted for example within the required volume of smart shelf RFID readers or used in portable RFID readers while being capable of mitigating multipath reflection issues and incorrect reading of RFID.